MHC‐Ig induces memory T cell formation in vivo and inhibits tumour growth. Issue 3 (11th November 2014) - Schütz, Christian; Zoso, Alessia; Peng, Shiwen; Bennett, Jonathon D.; Schneck, Jonathan P.; Oelke, Mathias
Abstract Induction of a T cell mediated immune response is critical for the eradication of viral infections and tumours. Soluble peptide‐loaded major histocompatibility complex‐Ig (pep−MHC‐Ig) have been shown to bind their cognate ligands, T cell receptor, with high affinity, and are successfully used to visualize antigen‐specific T cells. Furthermore, immobilized pep−MHC‐Ig can activate and expand antigen‐specific T cells in vitro and in vivo. In this study, we investigate the use of pep−MHC‐Ig as a potential strategy to modulate antigen specific T cell immune responses in vivo. SIY−Kb‐Ig immunization, together with the pre‐activation by an anti‐CD40 monoclonal antibody, is able to stimulate a strong expansion of adoptively transferred 2C transgenic T cells and the formation of long term antigen‐specific memory T cells. In addition, mechanistic studies show that the pep−MHC‐Ig molecules directly activate T cells in vivo without requiring uptake and reprocessing by antigen‐presenting cells. Furthermore, B6 mice immunized with pep−MHC‐Ig molecules inhibit tumour growth in a B16‐SIY melanoma prevention model. Thus, soluble pep−MHC‐Ig molecules represent a powerful tool for active immunotherapy.